Screening, characterisation and prevention of Hepatitis B virus (HBV) co-infection in HIV-positive children in South Africa - Jooste, P; van Zyl, A; Adland, E; Daniels, S; Hattingh, L; Brits, A; Wareing, S; Goedhals, D; Jeffery, K; Andersson, M; Goulder, P; Matthews, P (Elsevier, 2016)
Background In South Africa, the first HBV vaccine dose is administered at age 6 weeks, leaving a potential window for vertical transmission. Insights into HBV seroprevalence in the vulnerable HIV-infected group are important to drive improvements in surveillance, treatment and prevention. Objectives We set out to implement a screening program for HBV among HIV-infected children and adolescents in Kimberley, South Africa. Our aims were to demonstrate that screening is feasible and sustainable, to establish the prevalence of HBV, to characterise the HBV cases we identified, and to inform discussion about the infant vaccination schedule. Study design We tested all HIV positive children (age 0-16) for Hepatitis B surface antigen (HBsAg), delivering this testing as part of routine state-funded care. We followed up HBsAg-positive cases with an extended panel of HBV serology tests, and HBV DNA viral load quantification. Results Our screening campaign was successfully incorporated into routine out-patient care. Among 625 patients tested, we found five positive for HBsAg (0.8%), of whom three were Hepatitis B e-antigen positive. Two additional children initially tested HBsAg-positive but were negative on repeat testing. Antiviral therapy in the HBsAg children was reviewed and adjusted if required. Conclusions The results testify to the overall success of the HBV vaccine campaign. However, we have demonstrated that ongoing vigilance is required to detect cases and prevent transmission events. Further evaluation of the optimum timing of the first vaccine HBV vaccine dose is required; a vaccine dose at birth could reduce prevalence further.